Effect of rapid urbanization on Mediterranean karstic mountainous drainage basins. (November 2019) - Anker, Yaakov; Mirlas, Vladimir; Gimburg, Alexander; Zilberbrand, Michael; Nakonechny, Faina; Meir, Itzhak; Inbar, Moshe
Highlights: The Shiloh basin urbanization effect was evaluated as a model for the Yarkon Taninim recharge area and for similar mountainous karstic regions. By data fusion from various origins and types, it is shown that the Shiloh basin urbanization process is altering the natural hydrological regime. The Shiloh basin urbanization outcome is more runoff that is manifested in stronger flash floods and by less groundwater recharge. It is suggested that low impact draining facilities application in the urban development may help preserving regional hydrological balanced. Abstract: Transformation of permeable natural areas into impervious surfaces ( e.g. roads, parking lots, and buildings) is altering the watershed response to precipitation, generating bigger runoff volumes with increased peak discharges. The runoff travels faster to the watershed outlet, accumulates, and might cause flooding. Urban areas are affected by flooding, with consequences that might result in severe economic damage and even hazard to life. The paper will estimate the effect of rapid urbanization on runoff and on groundwater recharge. The model includes the Shiloh catchment basin located in a karstic mountainous terrain in Israel for a time period of rapid development from 1978 to 2018. Evaluation of surface permeability was based on land-use classifications from Landsat datasets using the Q-GIS 3.4 platform. Multiyear runoff coefficient estimation was calculated based on annual runoff and rainfall series. The evaluation suggests natural permeable areas were constantly declining from about 400 km 2 (nearby 100% of the Shiloh basin) in 1978 to about 100 km 2 in 2018 and that nonpermeable areas increased to 95 km 2 and semi-permeable areas to 250 km 2 . Despite annual precipitation decrease during the last two decades, the annual runoff coefficient has a pronounced tendency to increase. This research suggests that the anthropogenic impact on the Shiloh basin and, hence, similar watersheds encourages runoff accumulation, resulting in extreme flood events recurrence while significantly reducing the groundwater recharge.